2019
DOI: 10.1002/cpt.1625
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Stroke Prevention: A Population‐Based Cohort Study on Anticoagulation and Antiplatelet Treatments, and the Risk of Death or Recurrence

Abstract: Using claims databases of a public healthcare program (Quebec) for the years 2010–2013, we conducted a cohort study of patients with acute ischemic stroke (AIS) to describe secondary prevention treatments and determine how they stood against practice guidelines. We compared the risk of death or AIS recurrence over 1 year in patients treated with anticoagulants, antiplatelets, and/or other cardiovascular drugs. In the month after discharge, 44.3% of the patients did not receive the recommended treatment and >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Faure et al. ( 2020 ) reported that 36% of patients received ≥2 antiplatelets or a combination of antiplatelet and anticoagulant. Such combinations are not recommended because of the potential increased risk of bleeding (Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Faure et al. ( 2020 ) reported that 36% of patients received ≥2 antiplatelets or a combination of antiplatelet and anticoagulant. Such combinations are not recommended because of the potential increased risk of bleeding (Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…11% (95% CI: 2%−19%) of patients did not receive any antithrombotic medications as recommended (Figure 5). Faure et al (2020) reported that 36% of patients received ≥2 antiplatelets or a combination of antiplatelet and anticoagulant. Such combinations are not recommended because of the potential increased risk of bleeding (Table S1).…”
Section: Optimal Treatmentmentioning
confidence: 99%
“… 35 Compared with the untreated group, patients treated with anticoagulants and antiplatelets had reduced risks of death and recurrence from ischemic stroke (by 73% and 75%, respectively). 36 However, the use of secondary prevention medications for cardiovascular disease (ie, coronary heart disease or stroke) is low worldwide (antiplatelet drugs, 25.3%; β blockers, 17.4%; angiotensin-converting enzyme inhibitors or angiotensin-II receptor blockers, 19.5%; and statins, 14.6%), especially in low-income countries and rural areas. 37 The use of antiplatelet and lipid-lowering treatments for secondary prevention has been shown to decline significantly after discharge from hospital in urban areas of China.…”
Section: Discussionmentioning
confidence: 99%
“…After ischemic stroke, the activation of platelets can exacerbate microcirculation disturbances and ischemic brain tissue damage via neurotoxic substances or platelet aggregation. Thrombosis of the common carotid artery in rats can cause transient platelet aggregation, which can significantly expand the cerebral infarction area caused by global cerebral ischemia [35].…”
Section: Inhibiting Platelets and Coagulationmentioning
confidence: 99%